Athlete and support staff views on menstrual cycle related needs through a mixed-method survey - Creating a framework for a Female Athlete Supportive Environment - Mäkinen, A. (Haaga-Helia University of Applied Sciences, 2025)
While many hindering factors and barriers regarding the menstrual cycle related female athlete support have been identified in previous research, a more comprehensive and practical approach to female athlete specific support is yet to be taken.